nalisis Penimbunan Overburden pada Pit 3 Timur Tambang Banko Barat di PT Bukit Asam Persero (Tbk): Analysis of Overburden’s Stockpiling on Pit Mines 3 East Banko Barat at PT Bukit Asam(Persero) Tbk - Manurung1,, Ben Paulus; Tono, E.P.S.B Taman (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2018)
PT Bukit Asam (Persero) Tbk is one of the BUMN which is engaged in coal mining. This research was conducted in Pit 3 East West Banko operated by the contractor. The process of stripping overburden the difference in volume measurement survey overburden calculations progress ritation conveyance of overburden in one period, this can cause losses, therefore analysis overburden dumps.The study was conducted through a survey progress overburden, by measuring the elevation of each stage disposal area using Global Positioning System (GPS), then processed using Software Minescape to get volume of the preliminary draft and volume accumulation from February to October 2016 and then compared with the volume of every ritation to get a correction of cargo carrying means of each ritation. Testing of native soil specific gravity and material of disposal area to get a percentage compaction ofmaterial.The results showed the initial draft disposal volume amounted to 2,508,449.9 m3, the actual volume of hoarding February - October 2016 amounted to 2,130,080.3 m3, the total volume of production of means of conveyance before the compaction of 2,353,206 BCM. Value shrinkage percentage the disposal’ material of 9,3%, so that volume production of means of conveyance after compaction into 2,134,357.84 CCM, then it can be seen that the correction charge each ritasi his conveyance of 23,744 BCM.